Experimental studies of the image segmentation method quality from unmanned aerial vehicles based on the ant colony optimization algorithm under the influence of additive gaussian noise - Khudov, Hennadii; Makoveichuk, Oleksandr; Khizhnyak, Irina; Varvarov, Valerii; Zots, Fedir (Національний технічний університет "Харківський політехнічний інститут", 2025)
The subject matter of the article is experimental studies of the image segmentation method quality from UAVs based on the Ant Colony Optimization algorithm under the influence of additive Gaussian noise. The goal is to reduce the probability of first and second type errors in image segmentation by applying a segmentation method based on the Ant Colony Optimization algorithm under the influence of additive Gaussian noise. The tasks of the study are to evaluate the robustness and accuracy of the image segmentation method based on the Ant Colony Optimization algorithm under varying levels of additive Gaussian noise, and to compare its performance with the classical Sobel filter–based segmentation approach. The methods used are digital image processing techniques, statistical analysis of segmentation quality, implementation of the Ant Colony Optimization algorithm for image segmentation, modeling of noise-contaminated conditions, and comparison of segmentation errors of the first and second kinds. The following results are obtained: the method based on the Ant Colony Optimization algorithm demonstrates superior noise resistance and maintains higher accuracy than the Sobel filter approach. Specifically, it reduces first-kind segmentation errors by 14–23% and second-kind errors by 9–17%, depending on the level of noise. Visual and quantitative analysis confirms the effectiveness of the proposed method in processing UAV-acquired imagery affected by additive Gaussian noise. Conclusions.

Предметом статті є експериментальні дослідження якості методу сегментування зображень з БпЛА на основі алгоритму оптимізації мурашиної колонії під впливом адитивного гаусового шуму. Метою статті є зниження ймовірності виникнення помилок першого та другого роду при сегментуванні зображень шляхом застосування методу сегментування на основі алгоритму оптимізації мурашиної колонії в умовах дії адитивного гаусового шуму. Завдання дослідження полягають у тому, щоб оцінити стійкість і точність запропонованого методу сегментування при різних рівнях адитивного гаусового шуму, а також порівняти його ефективність із класичним методом сегментування на основі фільтра Собеля. Використані методи включають: методи цифрової обробки зображень, статистичний аналіз якості сегментування, реалізацію алгоритму оптимізації мурашиної колонії, моделювання умов зашумлення та порівняння помилок сегментування першого і другого роду. Отримані результати: метод на основі алгоритму мурашиної колонії демонструє вищу стійкість до шуму та забезпечує кращу точність сегментування порівняно з методом Собеля. Зокрема, кількість помилок першого роду знижується на 14–23 %, а другого роду – на 9–17 % залежно від рівня шуму. Візуальний та кількісний аналіз підтверджують ефективність запропонованого підходу для обробки зображень з БпЛА, заздалегідь спотворених адитивним гаусовим шумом.
Експериментальні дослідження якості методу сегментування зображень з безпілотних літальних апаратів на основі алгоритму оптимізації мурашиної колонії під впливом адитивного гаусового шуму
Keywords: UAV imagery; image segmentation; additive gaussian noise; ant colony optimization algorithm; quality of segmentation; errors of the first and second kinds; зображення з БпЛА; сегментування зображення; адитивний гаусів шум; мурашиний алгоритм; якість сегментування; помилки першого та другого роду